DIRECTION OF IMPRESSIONISM IN FINE ARTS - Sayfullayeva Barno (American Journals, 2023)
This article is about the direction of impressionism in visual arts. The author clarified the problem on the basis of existing scientific literature, relying on cultural information and written sources. He made a comparative analysis of existing specific approaches and theories in the direction of impressionism in visual arts.
Keywords: Impressionism, fine art, painting, classics.